Dr. Edwin Wright Letters: E. H. Ted Nagle - (Author); (Interviewer); (Publisher) (1970)
Letter - This letter was written in 1970 by Mr. E. H. Nagle. He recounts his personal history including his father working as a fur trader in Athabasca in 1883. Mr. Nagle describes growing up along the river, the difficulties of early travel, including remembrances of when the roadbed was first laid from Morinville. His father, Ed Nagle, staked the first claims (8) on Pine Point in 1898. Other mining ventures and stories of Mr. E. H. Nagles' early life are shared in this letter (2 pages)